Another world is possible : spiritualities and religions of global darker peoples - Hopkins, Dwight N.; Lewis, Marjorie (London ; Oakville, CT : Equinox Pub., 2009)
"Another World is Possible: Spiritualities and Religions of Global Darker Peoples represents voices of darker skin peoples throughout the world. What they have in common is their mobilizing their own created religions and spiritualities to forge self-identities. Some claim direct links to centuries of indigenous spiritual practices which have survived relatively in tact despite the invasion of foreign religions. Others have appropriated externally introduced religions and greatly modified these belief systems by combining or syncretizing them with indigenous perspectives and practices. All authors indicate the celebration and positive utility of their communities' spiritualities and religions. Without them, not only would individuals have died, but entire cultures and contexts would have perished. Thus, religion and spirituality suggest survival and pragmatic purposes. From creation narratives to Trickster heroes and heroines, spirituality and religion incarnate meaning, as well as fashion meaning so that humans can make surviving and thriving sense of the ecology and all breathing realities. The gods, God, and ancestors give life to peoples and their cultures, ecologies, and economies, all in the service of aiding the human community to be more fully human as servants to what spiritualities and religions have facilitated on earth. This book speaks to the progressive role of spiritualities and religions for today. In that sense, it is a gift to the world from the darker skin peoples globally."--Page 4 of cover.
pt. I. India. The untouchable "Dalits" of India and their spiritual destiny / B.M. Leela Kumari -- Dalits in India : key problems/issues and role of religion / James Massey -- pt. II. Japan. Recovering Jesus for outcasts in Japan / Teruo Kuribayashi -- pt. III. Australia. Providing a pathway to freedom / Hohaia Matthews Tjinatjunanyi -- Spirituality / Anne Pattel-Gray -- pt. IV. Hawaii. The Hawaiian situation : an overview of Hawaii's people, politics, religion, spirituality, and culture, yesterday and today / Toni G. Bissen -- pt. V. England. Theology, violence and the "other" / Anthony Reddie -- Another kind of black / Kate Coleman -- pt. VI. South Africa. "Impoverished on harvesting ground!" : Ruth 3 and African women in an HIV-positive South Africa / Madipoane Masenya (Ngwan'a Mphahlele) -- pt. VII. Botswana. HIV+ feminisms, postcoloniality and the global AIDS crisis / Musa W. Dube -- Soliloquy of a troubled heart : trying to make sense of senseless femicide / Dumi Oafeta Mmualefe -- pt. VIII. Zimbabwe. Ritual and spirituality among the Shona people / Beauty R. Maenzanise -- Economic "shortage" as a theologico-political problem in Zimbabwe / Edward P. Antonio -- pt. IX. Ghana. "Poverty is madness" : some insights from traditional African spirituality and mental health / Elizabeth Amoah -- Spiritual challenges of widowhood symbolism in an African religio-cultural setting : a Christian theological perspective / Emmanuel Martey -- Sex and sexuality in an African worldview : a challenge to contemporary realities / Rose Mary Amenga-Etego -- pt. X. Cuba. Eco-feminism and Yoruba religion in Cuba : a proposal for inter-religious dialogue / Luis Carlos Marrero Chasbar -- Black people and the church / Izett Sama Hernandez -- pt. XI. Jamaica. Social conditions and spiritual solutions in the Caribbean / Lewin Williams -- The church and the Jamaican society / Marjorie Lewis -- pt. XII. Brazil. Black spirituality : the anchor of Black lives / Antonio Sant'Ana -- Black heritage in Brazil / Diana Fernandes Dos Santos -- pt. XIII. USA. Womanist theology and epistemology in the postmodern U.S. context / Linda E. Thomas -- A home-place : self-identity and God in African American culture / Kirstin Boswell Ford -- Black Christian worship : theological and biblical foundations / Dwight N. Hopkins.
Includes bibliographical references (pages 371-372) and indexes.
Print version record.
Master record variable field(s) change: 082
Keywords: Blacks -- Religion; Religions; Spirituality; Religion; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Blacks -- Religion; Religions; Spirituality; Electronic books; Electronic books